CanSat outreach for post-secondary school students - Soh, Alan Jun Yuan (2016)
This final report documents the author’s progress and result of his Final Year Project on CanSat Outreach for Post-Secondary School Students. Due to the lack of interest in the field of engineering shown by local students, NTU look to offer more workshops and outreach programs to prospective students during the school holidays to spark interest in engineering. The existing CanSat outreach program is one of the many programs being offered. Through this project, the author aims to develop a cost effective yet interactive program for students, allowing exposure to computing and electronics. Various programming languages are included in this project, such as C/C++, Python and Java. Comprehensive manuals are provided to students for guidance throughout the workshop. Students are encouraged to express their creativity through designing of parachutes and editing of programming codes for data analysis. Through implementation of the deliverables of this project in future outreach programs, the author aspires to help students develop passion for engineering. Results and analysis can be found enclosed in this final report.